1999
DOI: 10.1017/s1357729800051122
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and nutritional effects on age at first oestrus of gilts selected for components of efficient lean growth rate

Abstract: Ages at first behavioural oestrus and at elevated plasma progesterone concentration were measured in three selection groups, after seven generations of divergent selection for lean growth rate (LGA), lean food conversion (LFC) and daily food intake (DFI) in a population of Large White pigs. First physiological oestrus was defined to have occurred when a blood plasma progesterone concentration of at least 1 μg/l was detected from weekly sampling of gilts. The study consisted of 146 gilts, which were given 0·75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…As in our study, Rozeboom et al (1995) reported large ranges in weight, backfat depth, growth rate, and lean and fat growth rate at the onset of puberty. In contrast to evidence that selection for lean growth delayed puberty onset in gilts (Rydhmer et al, 1992), our data support the results of Cameron et al (1999) and suggest that lean growth rate from approximately 50 kg until the initiation of puberty stimulation has no effect on age at puberty. It has been suggested that protein mass may be a regulator of reproductive performance (Cia et al, 1998).…”
Section: Lpsupporting
confidence: 71%
See 1 more Smart Citation
“…As in our study, Rozeboom et al (1995) reported large ranges in weight, backfat depth, growth rate, and lean and fat growth rate at the onset of puberty. In contrast to evidence that selection for lean growth delayed puberty onset in gilts (Rydhmer et al, 1992), our data support the results of Cameron et al (1999) and suggest that lean growth rate from approximately 50 kg until the initiation of puberty stimulation has no effect on age at puberty. It has been suggested that protein mass may be a regulator of reproductive performance (Cia et al, 1998).…”
Section: Lpsupporting
confidence: 71%
“…Rydhmer et al (1992) and Beltranena et al (1993) suggested that high lean growth rates may delay the onset of puberty. In contrast, Kerr and Cameron (1998) and Cameron et al (1999) suggested that selection for lean growth rate had no adverse affects on sexual development.…”
Section: Introductionmentioning
confidence: 93%
“…Growth rate relative to sex and interactions between sex and genotype may also be important in influencing meat quality in general. Selection for performance traits including growth rate and lean tissue in the carcasses of pigs over the period 1976-1995 in Denmark was shown by Oksbjerg et al (2000) to have given only a very small deterioration in meat quality, a finding which is essentially similar to that of Cameron et al (1999) in selecting for components of lean tissue growth over seven generations in populations of Large White pigs. Nevertheless, introducing genes from another breed in crossbreeding programmes (but obviously depending on the breeds involved) can affect meat quality.…”
Section: Tendernessmentioning
confidence: 88%
“…The rearing and mating procedures for the gilts are fully described by Cameron et al, (1999). During gestation, four gilts were housed in the same pen and fed in individual stalls twice-daily.…”
mentioning
confidence: 99%